Predictors of Knowledge Management in Healthcare Organizations in Butembo (International Forum Journal, 2020)
Having the right knowledge to act and decide has become very crucial in the 21st century and particularly for healthcare organizations where medical errors can cause millions of injuries (Ghosh & Scott, 2006). Effective knowledge management (KM) improves the quality of care provided by medical doctors and nurses. This research intended to assess the effect of change readiness, organizational culture, organizational ethical climate, and KM processes on KM effectiveness in healthcare organizations. Questionnaires were distributed to 220 nurses and physicians from Butembo, one of the towns in the eastern part of the Democratic Republic of Congo. One hundred thirty respondents returned the questionnaires, among which 117 were found valid. Multiple regressions were done to test the research hypotheses. The analysis revealed that structural readiness and organizational culture predicted KM processes. Structural readiness and KM processes predicted KM effectiveness. However, psychological readiness failed to predict KM processes and KM effectiveness. The findings suggested that hospitals should foster a culture of learning, risk-taking, and team-working to provide appropriate services to patients. They should also invest in developing KM processes such as knowledge acquisition and sharing.
Keywords: knowledge management processes; knowledge management effectiveness; change readiness; organizational culture; Butembo; Democratic Republic of Congo